6x(3x+5)=36

Simple and best practice solution for 6x(3x+5)=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x(3x+5)=36 equation:



6x(3x+5)=36
We move all terms to the left:
6x(3x+5)-(36)=0
We multiply parentheses
18x^2+30x-36=0
a = 18; b = 30; c = -36;
Δ = b2-4ac
Δ = 302-4·18·(-36)
Δ = 3492
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{3492}=\sqrt{36*97}=\sqrt{36}*\sqrt{97}=6\sqrt{97}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(30)-6\sqrt{97}}{2*18}=\frac{-30-6\sqrt{97}}{36} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(30)+6\sqrt{97}}{2*18}=\frac{-30+6\sqrt{97}}{36} $

See similar equations:

| (7x-2)(7x+2)=0 | | (7a-2)(7a+2)=0 | | 5-3x+1=4x-1 | | (7m-2)(7m-2)=0 | | x+x(3)x-5=85 | | 2t=3*8 | | 3x+1x–9=x | | 3*2+1d=28 | | 6(d+5)=30 | | y2+2y-840=0 | | 2*3b-2*9=2*3+1*3b | | 2(x-1)=5(x+4) | | (Y-6)(y+3)=0 | | 9z+2=29 | | 6x-20=10x+8 | | x-3=2(x-4)-1 | | 0.75c=21 | | 119=5•x+34 | | 5x^2=4137 | | (5x)x=4137 | | 7u-63=7 | | X=6*(0.5*x) | | (18x-5)+(8x+3)=180 | | 7x^2=-11x | | 4a+5=3a-2 | | 2x+4/9=5-x/3 | | 2a*2+6a-8=0 | | 2a^2+6a-8=0 | | 10-x÷4=7 | | 8x+15=12x+15 | | 5(4w+3)/3=-8 | | x/6-9=-5 |

Equations solver categories